Meningkatkan Kualitas Interaksi Belajar Mengajar Manajemen Kurikulum di Sekolah/Madrasah - Hermawati, Adetiyah Syahputri; Setiawan, Farid; Putri, Sheriena Maga; Zain, Raihan; Adli, Al A’raaf Wira (TSAQOFAH, 2022)
The school curriculum is a series of learning experiences created for school students to complete their educational goals. For that, it requires the right management pattern called curriculum management. A school/madrasah institution will always be favored by the community if it is well-operated/run, serves students who are fully willing to embrace the aspirations of the community and most importantly, the products that postgraduate institutions can offer. independent and competitive in the world of work. In order to get maximum results can not ignore the management agreement. An example is curriculum management that is in the spirit of the eight national education standards. This curriculum will be a reference/guideline for educational institutions/madrasahs in implementing learning. The process of structuring the curriculum will be very helpful and will bring more religious values ​​if it is associated with the values ​​of Islamic education. In this article, we will study the handling of the curriculum from the perspective of scholars, the Hadith of the Prophet and the Qur'an.